ANALYSIS OF FACTORS INFLUENCING HEALTHY BEHAVIOR OF THE ELDERLY BASED ON THEORY OF PLANNED BEHAVIOR IN PANTAI LABU DISTRICT, DELI SERDANG - Masdalifa Pasaribu (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2022)
This study aims to analyze the factors that affect the healthy behavior of the elderly in Pantai Labu District, Deli Serdang, based on the Theory of Planned Behavior (TPB). A quantitative approach was used involving 316 respondents who were selected by stratified random sampling. Data were collected through questionnaires and analyzed using multiple linear regression and path analysis. The results showed that attitudes towards healthy behavior, subjective norms, and perceived behavior control significantly influenced the intention to behave healthily. This intention is the main predictor of healthy behavior of the elderly. Attitude has the greatest influence on intention, followed by subjective norms and perceived behavioral control. These findings support the theory of the SDGs and suggest that health interventions for the elderly should be focused on improving positive attitudes, social support, and self-control. This research provides important recommendations for the development of more effective elderly health programs, as well as policies that support access and age-friendly health facilities. These results are also relevant to be applied in similar contexts in other regions.